THE EFFECTIVENESS OF DIGITAL MARKETING TRAINING PROGRAMS IN ENHANCING THE COMPETITIVENESS OF CULINARY MSME PRODUCTS IN TANGGULANGIN SUBDISTRICT - Ardianti, Elza Dwi Nur; Rodiyah, Isnaini (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the effectiveness of government-sponsored digital marketing training programs in enhancing the competitiveness of culinary small and medium enterprises (SMEs) in Tanggulangin Subdistrict, particularly those specializing in processed milkfish products, a local specialty. Method: A descriptive qualitative approach was employed using interviews, observations, and documentation, with data analyzed through the Miles and Huberman interactive model. The program’s effectiveness was evaluated based on Sedarmayanti’s (2014) framework, which includes input, process, output, and outcome indicators. Results: The findings reveal that the training has led to improved understanding of digital marketing, enhanced promotional skills through social media, and increased willingness to utilize online marketplaces. Nonetheless, challenges persist, such as overly theoretical materials, limited facilities, and insufficient post-training support. Long-term impacts, including sales growth and improved business efficiency, are emerging but remain constrained by inadequate technological access and financial assistance. Novelty: This study contributes to the limited empirical evidence on the practical impact of digital marketing training for local SMEs by integrating a contextual evaluation framework and emphasizing the need for sustained mentorship and infrastructure development to achieve long-term competitiveness.